2013
DOI: 10.1104/pp.113.230052
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Rice MicroRNAs Are Involved in Immunity against the Blast Fungus Magnaporthe oryzae

Abstract: MicroRNAs (miRNAs) are indispensable regulators for development and defense in eukaryotes. However, the miRNA species have not been explored for rice (Oryza sativa) immunity against the blast fungus Magnaporthe oryzae, the most devastating fungal pathogen in rice production worldwide. Here, by deep sequencing small RNA libraries from susceptible and resistant lines in normal conditions and upon M. oryzae infection, we identified a group of known rice miRNAs that were differentially expressed upon M. oryzae inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
300
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(311 citation statements)
references
References 82 publications
8
300
1
2
Order By: Relevance
“…However, the mechanisms of sRNA-mediated immunity remain largely elusive, especially for host-fungi interactions. In rice cultivars that are susceptible to Magnaporthe oryzae, enhanced resistance could be achieved by overexpressing miR160 and miR398 [37]. MicroRNA160 targets auxin-responsive factor 16 (ARF16), and miR398 regulates superoxide dismutase 2 (SOD2), both known defence-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms of sRNA-mediated immunity remain largely elusive, especially for host-fungi interactions. In rice cultivars that are susceptible to Magnaporthe oryzae, enhanced resistance could be achieved by overexpressing miR160 and miR398 [37]. MicroRNA160 targets auxin-responsive factor 16 (ARF16), and miR398 regulates superoxide dismutase 2 (SOD2), both known defence-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, osa-miR7695 was reported to mediate the negative regulation of natural resistanceassociated macrophage protein 6 (OsNramp6) to rice blast (Campo et al 2013). And, overexpression of miR160a and miR398b enhanced plant resistance by restraining the fungal growth (Li et al 2014). Moreover, it has been verified recently that osa-miR169 negatively regulates rice immunity by differentially repressing its target genes, the NF-YA family members (Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are one of the most abundant small RNAs (sRNAs) in plants and their typical lengths are 18-25 nucleotides (Li et al 2014). They are a group of endogenous, non-coding sRNAs involved in regulating gene expression mainly via repressing the translation or mediating the cleavage of target mRNA at the post-transcriptional level (Campo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Once they bind to their target sequences, miRNAs can trigger mRNA degradation or translational repression, causing down-regulation of the target genes. With the fast expansion of high-throughput sequencing platforms, genome-wide identification and differential expression analysis of miRNAs have been accomplished in an increasing number of plant species (Zhang et al, 2011;Li et al, 2014). Despite the large number of miRNA genes showing differential expression under various developmental and stress conditions, only few of these miRNAs have been functionally characterized.…”
mentioning
confidence: 99%
“…For example, overexpression of rice miR398b resulted in increasing plant susceptibility to P. syringae via inhibiting callose deposition (Li et al, 2010). In contrast, miR398b overexpression can also enhance plant resistance against the blast fungus Magnaporthe oryzae via increasing the production of hydrogen peroxide (Li et al, 2014). Similarly, it has been shown that miR863-3p can mutually regulate negative and positive mediators of defense signaling in a pathogen infection stage-specific fashion to fine-tune the timing of defense response (Niu et al, 2016).…”
mentioning
confidence: 99%